ANALISIS PERILAKU MASYARAKAT TERHADAP ANGKA BEBAS JENTIK DAN DEMAM BERDARAH DENGUE DI KECAMATAN PEKANBARU KOTA, RIAU - Wiwi Hardayati; Aras Mulyadi; Daryono Daryono (Jurnal Ilmu Lingkungan, 2011)
This study have been conducted in Kecamatan Pekanbaru Kota, on October-December 2009. Theaim of this research is to know relationship of the community behavior towards free larva index(ABJ) and dengue haemorrhagic fever (DBD). The relationship among education level andeconomy status of community with behavior monitoring free larva index (ABJ) were significant.The others factors (knowledge, attitude, available of infrastructure, and instruction) were notsignificant.